Waqf practices and its sustainability: the case of Universiti Sains Islam Malaysia - Gamon, Alizaman Dumangcag; Tagoranao, Mariam Saidano; Muhammad Zain, Lutfi (UNIDA Gontor Press, 2020)
Waqf practices in the higher education has been adopted in the past centuries by well-known Islamic universities in the world for educational financial sustainability. In Malaysia, for the past few years, some of the government higher educational institutions have implemented the waqf system under the Malaysia Higher Education Blueprint 2015-2025 (MEB) to ensure the universities long-term sustainable funds. But before the MEB was implemented, the Universiti Sains Islam Malaysia (USIM) has developed its own Waqf Center in 2013 as a sustainable funding for the university’s programmes and activities. The USIM Waqf and Zakat Centre (PWZ) has been well-developed through its Cash Waqf, Site Waqf and Education Waqf programmes. The objectives of this paper will explore the sustainability of the University waqf programmes and activities to the students and other target group of beneficiaries. For this purpose, analysis of the waqf implementation in other higher educational institutions in the Southeast Asia region will be undertaken. In this study, the data collection will include observation, interview and library documents and texts. The result of the research will anlayse the impressive sustainability programmes and activities (students’ residential college, health specialist clinic, mosques, hospital and mobile clinic.) that have been implemented by USIM as mutawalli. The paper forms a part of an ongoing research on the importance of waqf in enhancing